THE CLASSIFICATION AND CONTROL OF NAVY EXPENDITURES. - Pierpont, W. K. (The Accounting Review, 1946)
Abstract In this article Navy expenditure classification by objects is considered. The Bureau of the budget prescribes an "object" classification by which budget estimates are to be submitted. Therefore, spending agencies provide an expenditure analysis by such objects to support their budget estimates and to meet the Bureau of the Budget's requirement for such a classification. This classification of expenditures by objects is accomplished in the Navy Department by coding disbursement and expenditure documents; procurement requisitions, contracts, etc., leading to public vouchers, the Analysis of Labor Roll Summary by Expenditure Classifications, a monthly report for labor similar to the Analysis of Materials Summary by Expenditure Classifications; and a Schedule of Collection Provision for this classification may be noted on the sample form of the Analysis of Materials Summary by Expenditure Classifications at the bottom of the form in a separate schedule. The object classification required by the Bureau of the Budget of all Federal departments permits the preparation of a statement of the total expenditures of the Federal government by broad classifications of expenditures. It may also he used to compare in a broad manner the operation of various departments in several respects, for example, the proportion of total expenditures charged for personal services.